Contact Stress Analysis of A Spur Gear Using Lewis And Hertz Theory - Oo, Than Zaw; Win, Htay Htay; Swe, War War Min; Aye, Yin Yin (The Indonesian Journal of Computer Science, 2026)
This paper focuses on the design and contact stress analysis of a spur gear for sugarcane juice extraction machine by changing gear face widths and three different materials (ASTM A 220-99, ASTM A 536-84 and C54400). Gear corrosion occurs at contact points as a result of bending stress and contact stress. This is the major source of the gear failure of the sugarcane juice extraction machine. This whole mechanism will be driven by a 1383W capacitor-start induction motor according to the motor power selection. Pitch diameters of 48 mm and module of 2.5 mm spur gear is selected in the design of gear. In theoretical analysis, the Lewis contact stress equation is used. In the numerical analysis, the geometry is created by SolidWorks software. The minimum von-Mises stress and effective strain are found that on ASTM A 220-99 material by using ANSYS 2020 R1 software. In this paper, von-Mises stress and effective strain are analyzed by changing the face widths of gears to 13 mm, 15 mm, 17 mm, 19 mm and 21 mm and using finite element analysis (FEA). Although all face widths are safe for this design, 17 mm is chosen in this paper due to power consumption and strength points of view.